EFFECT OF FYM, CROPPING SYSTEM, SOURCES AND LEVELS OF SULPHUR ON GROWTH ATTRIBUTES, YIELD AND PIGEONPEA EQUIVALENT YIELD IN PIGEONPEA + GROUNDNUT INTERCROPPING SYSTEM - JAT, RAMAVATAR; AHLAWAT, I.P.S. (Annals of Agricultural Research, 2014)
A field experiment was conducted during the rainy (kharif) seasons of 2003 and 2004 at IARI, New Delhi to study the response of pigeonpea + groundnut intercropping system to sources and levels of sulphur along with the FYM. Application of FYM increased the growth attributes and yield of both pigeonpea and groundnut and pigeonpea equivalent. However, intercropping did not have any impact of these parameters, except pigeonpea equivalent yield. Application of sulphur @ 35 and 70 kg S/ha, being on par, significantly improved the growth attributes, yield attributes and yield of both pigeonpea and groundnut and pigeonpea equivalent. Among the sources, cosavet recorded higher growth attributes and yield of pigeonpea and groundnut and pigeonpea equivalent yield over elemental sulphur and gypsum.